Instability Mechanisms for the F‐Region Plasma Irregularities Inside the Midlatitude Ionospheric Trough: Swarm Observations - Yiwen Liu; Chao Xiong; Xin Wan; Yeping Lai; Yuhao Wang; Xiao Yu; Ming Ou (Space Weather)
Abstract The midlatitude ionospheric trough (MIT) is a well‐known feature in the topside ionosphere. Previous MIT related studies mainly focused on the MIT structure itself, while few studies focused on irregularities inside the MIT region. In this study, we provided for the first time the magnetic latitude and magnetic local time distribution of irregularities within the MIT, by using the Swarm in situ plasma measurements. Orbital cases show that both the MIT equatorward and poleward walls are embedded with small‐scale irregularities. Further statistical analysis reveals that the particle precipitation is the dominant mechanism for the dayside MIT region irregularities, while nightside MIT region irregularities are strongly related with the temperature gradient drift instability. The Swarm observations show that the temperature gradient drift instability occur not only in MIT equatorward wall but also in MIT polarward wall, which is different to the theoretical prediction of Hudson and Kelley (1976, https://doi.org/10.1029/JA081i022p03913).